Teaching agile: A case study approach with an optional game - Chavarría, Juan A.; Flores, Javier; Lakshmikanth, Geethalakshmi S.; Paz, Ignacio (Journal of information technology teaching cases, 2024)
Learning Agile philosophy is essential for system analysis and design or software development courses. Organizations operate in highly dynamic environments, constantly needing to adapt, change, or create innovative Information Systems. Agile provides guiding values and principles that enable systems analysts to support organizations in responding to change and developing, modifying, or updating information systems. By learning Scrum, an Agile-inspired framework, students can assume the role of systems analyst, organizing activities and working in teams iteratively to solve complex problems using Agile principles. This hands-on approach helps students understand the importance of stakeholder involvement, constant scrutiny, and adjustment to achieve frequent system updates. Hence, this case study immerses students in a scenario where they apply the Scrum framework, with an optional puzzle game to introduce students to agile philosophy through its manifesto. Learning by doing has proven effective for complex or dry topics, with students responding positively to this method. Interview data collected at the end of the activity showed high student satisfaction and a strong sense of knowledge acquisition while enjoying the class. Additionally, integrating a game to internalize agile concepts with a teaching case to apply concepts presents a rich educational approach that can be adapted to other Information Systems topics.